Historical Perspective of Security Relations Between Kenya and Uganda from 1962 – 2024 - Okoth, Pontian Godfrey; Odulwa , Kenneth Kaunda; Wekesa, Peter Wafula (African Journal of Education,Science and Technology (AJEST), 2024)
Cross-border conflicts have led to the loss of many human lives and the displacement of various groups. The purpose of the study is to provide a historical perspective of security relations between Kenya and Uganda from 1962-2024. The study reviewed various literatures and a major gap was identified. Theoretically, the study adopted the ideas of bureaucratic theory propounded by Max Weber in 1921. Methodologically, due to the qualitative nature of the research, the study embraced historical research design because it helps in evaluating and relating the past occurrences in order to establish the causes, effects or trends of those occurrences with the aim of using the data to understand and explain the past or present and future anticipated events. The study found out that; first, the security relations between Kenya and Uganda during the 1960s characterized by a spirit of regional cooperation. Secondly, the independence and early relations between Kenya and Uganda in 1960s laid a solid foundation for future collaboration and partnership in matters of security. Lastly, Kenya and Uganda have collaborated on regional peacekeeping efforts, including deployments to conflict zones such as Somalia and South Sudan. In Conclusion, in assessing the security relations between Kenya and Uganda, it becomes clear that bureaucratic structures, processes and governance mechanisms play a crucial role in shaping bilateral cooperation and development.